Cardiovascular risk factors in children and adolescents with type 1 diabetes in Italy: a multicentric observational study. Issue 8 (27th September 2020) - Fornari, Elena; Piona, Claudia; Rabbone, Ivana; Cardella, Francesca; Mozzillo, Enza; Predieri, Barbara; Lo Presti, Donatella; Cherubini, Valentino; Patera, Ippolita Patrizia; Suprani, Tosca; Bonfanti, Riccardo; Cauvin, Vittoria; et al.
Abstract: Aims: To assess the prevalence of cardiovascular risk factors (CVRFs) and to identify the variables associated with CVRFs in a cohort of children and adolescents with Type 1 Diabetes. Methods: 2021 subjects, 2‐18 year‐old, were recruited in 17 Italian Pediatric Diabetes Centers. Anthropometric, blood pressure, biochemical (HbA1c, lipid profile, ACR), insulin therapy, physical activity level, smoking and family socio‐economic status data were collected. CVRFs prevalence and their distribution were analyzed according to age and binary logistic regression was performed with positivity for at least one major CVRF (BMI‐SDS > +2SD, blood pressure > 90th percentile, LDL cholesterol>100 mg/dL) as dependent variable and age, duration of illness, gender, HbA1c and physical activity, as independent variables. Results: The prevalence of CVFRs not at the recommended target was respectively: 32.5% one CVRF, 6.7% two CVRFs and 0.6% three CVRFs, with no significant differences across the 3 age groups (2‐10, 10‐15, 15‐18 years). In the total sample, HbA1c and inadequate physical activity were associated with a higher probability of having at least one major CVRF. This probability was associated with physical activity in the 2‐10‐year‐old group, with physical activity and HbA1c in the 10‐15‐year‐old group and with HbA1c only in subjects older than 15 years. Conclusions: More than 30% of subjects had at least a major CVRF. Early detection of CVRFs may be useful to enforce the therapeutic intervention in this subgroup, in order to reduce the risk to develop cardiovascular complications.